Manual de seguridad e higiene para prevenir riesgos laborales en la empresa agricola bananera margarita del canton valencia - Hernandez Maldonado, Silvia Tatiana (2011)
This research was conducted in the Banana Margarita Agricultural Company was incorporated on March 2, 1970 by resolution issued by the Registry, under the RUC 0992359072001, Nueva Union, Valencia country, province of the Rios. The general objective of applied research in this company is to develop and implement HEALTH AND SAFETY MANUAL TO PREVENT AGRICULTURAL EMPLOYMENT IN THE COMPANY OF CANTON VALENCIA MARGARITA BANANA to confirm the reliability and accuracy of the protection and management tools for appropriate personal protection. To investigate the analytical method was used which allowed for the analysis of the current state of Human Resources management and the method which was obtained deductive reasoning to draw conclusions that are based on particular facts accepted as valid which were the absence of good practice in health and safety at Banana Margarita Company for which a solution was obtained considering the creation of the manual which is of general application. To carry out the fieldwork and in the direction to achieve the objectives the following are considered primary sources and secondary research techniques as well as direct observation, the survey collects data which facilitated a "sample" or fraction of the population under study considering 100% of the sample in this company because only 60 people working in agriculture and 9 people in administration. Addition, we used the analysis and interpretation of surveys with the aim of knowing what the degree of risk, through methods such as direct observation, the development of the flowchart which allowed risk score points in the process and so implement formats such as: risk Identification, Risk Assessment, risk control, risk mapping of Enterprise, Development of procedures manuals to help research the verifiable information to reach conclusions and solutions The author concludes that due to the risks identified under investigation the company must comply with the Ministry of Labour, Health and Safety IESS so you risk the physical safety of its workers it is recommended to implement the use of manual training plans, which will optimize the physical relationship in the work environment, creating appropriate conditions for workers to perform their duties in a healthy and effective, considering that the success or failure of the implementation of standards Health and Safety at Work will depend on all that make Banana Margarita.